Instagram Sebagai Medium Pesan Komunitas Ibu Tunggal di Indonesia (Studi Netnografi di Akun Instagram @singlemomsindonesia) - Ade Noviani; Sri Wijayanti (Jurnal Netnografi Komunikasi, 2022)
The virtual community of Indonesian Single Mothers on Instagram, Single Moms Indonesia (SMI), is an interesting study in relation to the development of technology and communication. The depiction of messages conveyed through social media Instagram @singlemomsindonesia in the context of themes, functions, and messages before and after the pandemic as well as the responses of followers on Instagram is one of the important and interesting things to study. For this reason, this study uses the netnographic method by using the concepts of group communication, virtual communities, persuasive messages, and social media as the analytical tools. The research data was obtained through analysis of posts on Instagram for the period November 2019 – June 2020 and in-depth interviews with followers of the Instagram account @singlemomsindonesia who are single mothers. The research findings show that the message themes that often appear are stories and messages for single mothers with a message function, namely social functions and the form of messages that often appear is conveyed in the form of posters. The response of Instagram followers @singlemomsindonesia showed a positive response through messages uploaded on Instagram, informants felt they had support from other parties. The SMI community on Instagram is the right place to convey messages to marginalized groups and maintain the existence of the community in the digital era as evidenced by the SMI community is one of the single mother virtual communities that has the most followers compared to others.